Gaya Komunikasi Dosen dalam Pembelajaran Mahasiswa - Mutawakkil Mutawakkil; Nuraedah Nuraedah (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2019)
The research aims to analyze the communication style to overcome the boredom of students’ learning in the social history course at History Education Program Study, Faculty of Teacher Training and Education, Tadulako University